Craft Education and Economic Development in the Valley of Kashmir during the Era of Sultan Zain-ul-Abidin Budshah - Reyaz Ahmad Bhat (PT. Radja Intercontinental Publishing, 2023)
Abstract: This research paper examines the interplay between craft education and economic development in the Valley of Kashmir during the reign of Sultan Zain-ul-AbidinBudshah. By investigating historical records, archaeological findings, and scholarly works, the paper analyzes the role of craft education in fostering economic growth, social mobility, and cultural enrichment during this era.